Spontaneous breaking of lepton number and the cosmological domain wall problem - Lazarides, George; Shafi, Qaisar (Physical review letters, 2019)
We show that if global lepton number symmetry is spontaneously broken in a postinflation epoch, then it can lead to the formation of cosmological domain walls. This happens in the well-known “Majoron paradigm” for neutrino mass generation. We propose some realistic examples that allow spontaneous lepton number breaking to be safe from such domain walls.